Performance Analysis and Optimization of a 6-DOF Robotic Crusher. (4th November 2020) - Li, Guoguang; Shi, Boqiang; Liu, Ruiyue; Gu, Jie
Abstract : Considering the complexity of multidimension parameters and the mechanical performance of a 6-DOF robotic crusher, a multiobjective optimization function based on the transmission index and condition number is established. As an important operation in the screw theory, the reciprocal product between the transmission wrench screw of an actuator and the output twist screw of the mantle assembly is used to represent the instantaneous power. The expression of transmission index is derived according to the principle that constraint wrench screws apply no work to the mantle assembly. It can be used as a criterion to evaluate the transmission performance. Then, based on the Jacobian matrix, the equation of condition number is constructed which provides a criterion for evaluating kinematic accuracy. Finally, the workspace and singularity of the 6-DOF robotic crusher are analyzed to verify the rationality of the optimized variables. The results show that the optimized structure can completely crush the material in the workspace and effectively avoid singularity, which provides a basis for practical application.